Multivariable predictive control of a distillation column - Cai, Yue Bin (2008)
In this thesis, a state space version of Generalized Predictive Control (GPC) is studied. The main feature of this scheme is the use of the Deterministic Least Squares framework for both the controller and the state estimator designs.